COMPREHENSIVE REVIEW OF HEALTH EDUCATION PROGRAMS IN ASSESSING CURRICULUM CONTENT, EFFECTIVENESS, AND CULTURAL SENSITIVITY IN PROMOTING HEALTH LITERACY AND BEHAVIOR CHANGE. - Mohammed Saleh Hadi Al Garea, Ali Haider Mahdi Alhottila, Marzoog Saleh Al Salaiea, Hamad Awaidah Hamad Al Salah, Saleh Mohammed Amer Al Mari, Mohammed Mana Saleh Alsalem Alyami, Faisal Hassan Salem Alyami, Rayid Hamad Hussein, (Chelonian Research Foundation, 2022)
Health education programs are really helpful in informing individuals about healthy behavioral changes and increasing health literacy among the diverse community. A comprehensive review of the health education programs carries out an inventory of their content and effectiveness, as well as their cultural sensitivity. This review is intended to look into the existing literature and research in order to draw insights into the strengths and limits of the current health education programs and offer suggestions for further improvements. Some of the main factors are the way the learning material is being organized, how to make it more effective, and the issues that may appear in culturally sensitive health education. Keywords: health education, curriculum content, effectiveness, cultural sensitivity, health literacy, behavior change.